Analysing the Impacts of Task-Based Language Teaching (TBLT) on Students’ Speaking Ability - Muhammad Syam Adegustian; Sofyan A. Gani; Hendra Heriansyah (Research in English and Education Journal, 2022)
As one of the four major skills in the English language, speaking is arguably the most important. However, learning to speak in English has been a problem to many English learners. This is because of issues caused by the lack of communicativeness in English classrooms. There have been numerous calls to solve these issues. More than one of them are calling to the use of a more communicative approach to teaching English. Task-Based Language Teaching (TBLT) has been a highly advocated approach to teach a language communicatively. This study aims to analyse the language learning approach by reviewing literatures, previous studies and experts’ perspectives on the approach in order to obtain as much relevant information as possible about its impacts on students’ speaking ability. Consequently, this study has found that TBLT impacts students’ speaking ability in ways beneficial and can do so in a variety of ways and conditions. This study’s finding on TBLT impacts on students’ speaking ability also means that it is highly suggested that speaking instructors and learners approach their teaching and learning the TBLT fashion.